Psychological Distress and Widespread Pain Contribute to the Variance of the Central Sensitization Inventory: A Cross‐Sectional Study in Patients with Chronic Pain. Issue 2 (11th December 2017) - van Wilgen, Cornelis P.; Vuijk, Pieter J.; Kregel, Jeroen; Voogt, Lennard; Meeus, Mira; Descheemaeker, Filip; Keizer, Doeke; Nijs, Jo
Abstract: Objectives: Central sensitization (CS) implies increased sensitivity of the nervous system, resulting in increased pain sensitivity as well as widespread pain. Recently, the Central Sensitization Inventory (CSI) was developed to assess symptoms of CS and central sensitivity syndromes. The aim of this study was to examine the convergent validity of the CSI by comparing the outcome to psychosocial factors and clinical features of CS. Methods: In a cross‐sectional explorative study, patients with chronic pain completed multiple questionnaires, including the CSI, Pain Catastrophizing Scale, and Symptom Checklist 90, for psychological distress, duration of pain, intensity of pain, widespread pain, and lateralization of pain. Based on bivariate correlations, relevant predictors of CS were selected and used to fit an exploratory structural equation model (SEM) of CS. Results: In total, 114 patients with chronic pain were included, 56.1% being women. The average pain duration was 88 months. The mean total score on the CSI was 36.09 (15.26). The CSI was strongly related to known contributing and related factors of CS. SEM analysis showed that both psychological distress and widespread pain contributed significantly to the variance in symptoms of CS in patients with chronic pain. Conclusion: In this study, the convergent validity of the CSI was measured with demonstration of a strong relationship between contributing factors and clinical features of CS. These findings of convergent validity, considering former studies of the CSI, underline the use of the questionnaire in the clinical practice.